STRATEGY COMMUNITY EMPOWERMENT THROUGH THE DEVELOPMENT OF TANI BETET TOURISM IN NGANJUK REGENCY, EAST JAVA - Defita Dwi Anggi; Agus Purnomo; I Nyoman Ruja (JURNAL SOCIUS, 2021)
The research aims to formulate a strategy for community empowerment by developing the Tani Betet Tourist destination in Nganjuk Regency,  East Java.  The method used is a quantitative method with SWOT analysis. The number of respondents was 20 people and one key informant. The number of respondents is as many as 20 people and key respondents 1 person. The results of this study are strategies used in community empowerment in Tani Betet Tourism, which are contained in quadrant I (Progressive Strategy). Strategies that can be done in the development of Tani Betet Tourism is to maximize the role of the community in supporting packaging and promoting tourism that has the opportunity to increase tourist visits. Utilization of community empowerment programs in sustainable tourism development. The active role of local governments is to give rise to trust in each other in society to accept the technological developments present. The benefits of this research provide strategies as a reference in optimizing community empowerment in Tani Betet Tourism, for tourism development through community empowerment programs.